Breed-typical front limb angular deformity is associated with clinical findings in three chondrodysplastic dog breeds - Lappalainen, Anu K.; Pulkkinen, Hanna S. M.; Mölsä, Sari; Junnila, Jouni; Hyytiäinen, Heli K.; Laitinen-Vapaavuori, Outi (Frontiers in Veterinary Science, 2023)
Angular front limb deformity (ALD) refers to an excessively curved limb conformation, which is seen in some chondrodysplastic dog breeds. Common characteristics of ALD include carpal valgus (VALG), front limb rotation (ROT), elbow incongruity, and lateral radial head subluxation. These may cause lameness and discomfort in affected dogs. The clinical impact and breed-specific characteristics of front limb conformation in chondrodysplastic breeds are unknown. This prospective and cross-sectional study aimed to investigate differences in front limb conformation between three chondrodysplastic breeds. We further evaluate whether front limb conformation is associated with clinical findings and limb function. We propose novel methods to classify findings in the interosseous space and to quantify lateral radial head subluxation. Data from a total of 224 front limbs from 112 dogs of three chondrodysplastic dog breeds (30 Standard Dachshunds, 29 Skye terriers, and 53 Glen of Imaal terriers) were included in the study. Front limb VALG and ROT were measured with a goniometer. From the radiographs, the elbow joint was graded for incongruity (INC), and the humeroradial angle (HRA) was measured to assess lateral radial subluxation. The association of front limb conformation with clinical signs and limb function was investigated using orthopedic examination, goniometric and kinetic measurements, and radiography. The breeds differed significantly in their front limb conformation. The Dachshund had the least ROT and the least radial head subluxation. The Skye terrier had the most VALG, the most radial head subluxation, and the largest prevalence of moderate and severe INC. The Glen of Imaal terrier had the most ROT. In addition, INC, ROT, VALG, and HRA were found to be independent of each other and were associated with several measurable clinical abnormalities and limb function such as pain, lameness, limited range of motion, and elbow joint osteoarthritis. This implies that VALG, ROT, and HRA could be used in addition to INC grading when choosing musculoskeletal characteristics of dogs suitable for breeding.